Out of Date. Remarks on the 1951 “Index of Books to be Immediately Excluded” - Dąbrowicz, Elżbieta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This article seeks to identify some of the uses of „the index of books to be immediately excluded” issued by the Ministry of Culture and Arts in 1951. At that time, decrees of the sort specified inventories of books permitted to be included on the shelves of Polish. In the process, many books were to be removed for good both from libraries and from native heritage. Additionally, the procedure of “purification”, as it was called by the officials, bore significant similarities to the repressive practices of the German and Russian occupants used during WWII. The author argues that analogies were drawn wittingly or impulsively at least for the effectiveness of German and Russian inventions. The 1951 list of books forbidden for the Polish common reader offers their obsolete character as the reason for exclusion. Up to date did not mean “contemporary” but up to the demands of state authorities. Administrative pressure to reflect the political agenda converted books into somewhat fatter newspapers and in this way seriously damaged book, which had always been the important vehicle of national and cultural memory.